The Influence of Family and Business Complexity on Succession Strategy : The Case of Indumeco - Alvarado, Hector (2025)
This thesis discusses the succession strategy of Indumeco, a family business in the construction sector, by using Gimeno’s Business Management Formula. This paper analyzes how family complexity, business complexity, and structure development can influence succession. With interviews, analysis of the company’s documentation, and contextual analysis, results were drawn on the structural risk of Indumeco, and recommendations were proposed to improve Indumeco’s governance structure and succession planning. This case study provides insights for similar family businesses in the Central America region.